Android-Based Car Tire Pressure Monitoring System - Andryanto Aman; Randy Angriawan; Zulfikar; Erwin Gatot Amiruddin (Ceddi Journal of Information System and Technology (JST), 2022)
Incorrect tire pressure measurements can cause rapid damage to vehicle tires. The measurement process has been done manually. Therefore, a system is needed that can monitor tire pressure on the car directly without having to measure the air pressure on the tire manually. The purpose of this research is to design and implement an android-based car tire pressure monitoring system This data was obtained through Field Research and Library Research. The method used in this research is to use the PIECES (Performance, Information/Data, Economic, Control/Security, Efficiency, and Service) methods. The results of his analysis research are used as a basis for improving the working system of tire pressure monitoring using handphone android to measure tire pressure by testing air pressure on car tires. The results of the research on the vehicle tire pressure measurement system can help the community, both for the middle class and for the rich, so this research is important to implement.